EDUCATIONAL BACKGROUND AND CAPABILITIES REQUIRED TO IMPROVE THE PERFORMANCE OF AUDITORS IN ACCOUNTING INFORMATION SYSTEMS: A CASE STUDY OF KAP AIS - Imelda Hotmaria (SEAN Institute, 2023)
Automation of the accounting recording process makes an auditor of an accounting information system needed. Information systems auditors generally come from three different educational backgrounds, namely information systems, information technology, or accounting. This study aims to analyze the competencies required to become an information systems auditor. The study begins by testing whether there is an effect of differences in educational background on auditor performance by using linear regression. The study used a sample of 71 accounting information system auditors who worked at AIS audit firms and interviewed partners from AIS audit firms. From the results of the study, there was no influence of educational background on auditor performance. Further, this study found that the need for knowledge or skills regarding auditing,